Abdominal massage as an adjunctive therapy for pediatric functional constipation: a randomized controlled trial - Malekiantaghi, Armen; Miladi, Mahdis; Shabani Mirzaee, Hosein; Tolou Ostadan Yazd, Mohamadreza; Eftekhari, Kambiz (The Turkish Journal of Pediatrics, 2025)
Background. Chronic functional constipation affects approximately 3% of children globally, leading to painful defecation, fecal incontinence, and abdominal discomfort. Abdominal massage may improve gastrointestinal motility by stimulating vagal activity and reducing abdominal muscle tension. This study aimed to evaluate the effectiveness of abdominal massage therapy as an adjunct treatment for chronic functional constipation in children.Methods. This randomized controlled trial included 61 children aged 4–10 years (mean age 6.36 ± 1.77) diagnosed with functional constipation. Participants were randomly assigned to two groups: the control group, receiving standard drug therapy, and the intervention group, receiving 12 sessions of Swedish abdominal massage involving effleurage and gentle pressing, vibration of the small and large intestines, kneading of the abdomen, and clockwise circular movements in addition to drug treatment. Outcomes assessed included stool consistency (using the Bristol Stool Scale), constipation severity (measured by the Constipation Assessment Scale), and associated symptoms.Results. Both groups showed improvements in stool consistency; however, no statistically significant difference was found between them. The intervention group demonstrated a significantly greater reduction in constipation symptoms (Constipation Assessment Scale scores decreased from 14.70 ± 1.29 to 10.21 ± 1.45, P < 0.001.) and fewer episodes of fecal incontinence (from 3.82 ± 1.33 to 2.70 ± 1.33 days/week, P < 0.001) compared to the control group.Conclusion. A 12-session abdominal massage therapy program appears to be an effective adjunct treatment to standard pharmacological therapy for alleviating constipation-related symptoms in children. Larger, multicenter trials are needed to confirm these findings.
Keywords: Swedish abdominal massage; children; chronic constipation; functional constipation; Bristol Stool Scale; Constipation Assessment Scale